2018
DOI: 10.15376/biores.13.2.2785-2799
|View full text |Cite
|
Sign up to set email alerts
|

Applying a GIS-based Fuzzy Method to Identify Suitable Locations for Solar Kilns

Abstract: The aim of this study was to identify suitable locations for solar kilns in Vientiane, the capital of Laos, based on geographical and climatic conditions and restricted areas. The criteria of the parameters, which were incorporated with Fuzzy membership functions, were used to create layers in the ArcGIS environment to draw maps of suitability. Climatic parameters, based on the Fuzzy method, were used to investigate the period of productive performance for solar kilns. The results showed a range of possible lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…where RHmi is the relative humidity at a specific time (hour) in measured on-site and RHNSi is the relative humidity measured by NASA (POWER Data Access Viewer v2.0.0). This method was introduced by Phonetip et al (2018b). This study used the temperature and relative humidity at 2 m above the ground, based on the available time extent, i.e., from 1981 until 2020 (39 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where RHmi is the relative humidity at a specific time (hour) in measured on-site and RHNSi is the relative humidity measured by NASA (POWER Data Access Viewer v2.0.0). This method was introduced by Phonetip et al (2018b). This study used the temperature and relative humidity at 2 m above the ground, based on the available time extent, i.e., from 1981 until 2020 (39 years).…”
Section: Methodsmentioning
confidence: 99%
“…Even in a relatively stable environment, wood is still subject to seasonal movement as humidity levels and temperatures change with the weather. For instance, EMC oscillation between January and December in Vientiane, Laos varies from 10% to 16% (Phonetip et al 2018b). Controlled indoor environments with functioning heating and air conditioning can help minimize these changes, but they still can present small changes, e.g., the door that sticks in winter or small gaps between the floorboards in summer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a Tectona grandis tree was selected for this experiment, conducted at the Faculty of Forest Science, National University of Laos (NUoL), from February until June, this period offering high solar radiation, as suggested by Simpson andTschernitz [4], and SSE [8] and is also known as the dry season in Laos [9]. Also, Phonetip et al [5] found that the Faculty of Forestry Sciences is one of the most suitable locations for drying timber using solar kilns. The tree was located at geographical coordinates of 18 ° 0.2 ' 21 "N and 120 ° 37 ' 45 "E, with 108 m above sea level.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
“…Considering the maximum temperature of 46 °C inside the compartment with the range of relative humidity value of 25 -50 %, the conditions could allow EMC at 4.5 -8.5 %, as per the EMC chart [14]. The EMC values were found to be much lower than the ambient conditions (11 -12 %) from December to March, and 14 % for April [5].…”
Section: Drying Conditionsmentioning
confidence: 99%
See 1 more Smart Citation